2011
DOI: 10.1007/s12282-011-0290-5
|View full text |Cite
|
Sign up to set email alerts
|

Curative-intent stereotactic body radiation therapy for residual breast cancer liver metastasis after systemic chemotherapy

Abstract: Liver metastases from breast cancer are generally treated with systemic therapy such as chemotherapy or hormonotherapy. However, local treatment options such as resection, radiofrequency ablation (RFA), and radiotherapy can also be considered to treat oligometastases. We report the case of a 45-year-old female treated with stereotactic body radiotherapy (SBRT) after chemotherapy against a solitary liver metastasis from primary breast cancer. A liver metastasis with diameter of 35 mm developed 3.5 years after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In sync-oligometastases of colon and rectal cancer, renal cell cancer also reportedly shows relatively favorable survival [1012]. In oligo-recurrence of breast cancer, patients are reported to achieve relatively favorable survival [14, 15]. Niibe et al reported that all seven of breast cancer patients with bone-only oligo-recurrence were still alive at the last followup (median followup, 40 months).…”
mentioning
confidence: 99%
“…In sync-oligometastases of colon and rectal cancer, renal cell cancer also reportedly shows relatively favorable survival [1012]. In oligo-recurrence of breast cancer, patients are reported to achieve relatively favorable survival [14, 15]. Niibe et al reported that all seven of breast cancer patients with bone-only oligo-recurrence were still alive at the last followup (median followup, 40 months).…”
mentioning
confidence: 99%
“…While considering the molecular characteristics, breast cancer can also be divided into the following four molecular subtypes: luminal A, luminal B, basal-like, and HER2 type, which indicate various molecular phenotypes and drug susceptibility. Irrespective of the subtype, the common development process of breast tumor can generally be divided into the following three phases: initiation, invasion, and metastasis. , The initiation and invasion processes involve the tissue in situ, which may be less harmful than a process such as metastasis. Tumor metastasis can be defined as the spread of tumor cells from one organ or part to another that is not directly connected to it, which leads to the progression and aggravation of tumorigenesis . Such a process can be artificially divided into the following five main steps: cancer cells invade nearby healthy cells; they penetrate into the circulatory or lymph system; they migrate through circulation; they lodge in the capillaries; and new small tumors grow. , In breast cancer, four main organs may be involved in metastasis (brain, bone, lung, and liver), and they have entirely different symptoms. Recent publications have confirmed that different breast cancer subtypes may have entirely different patterns of metastasis because they have different expression patterns of biomarkers such ER (estrogen receptor), PR (progesterone receptor), and HER2. , Hormone receptor positive tumors, which have the highest morbidity among different subtypes, have been reported to be more likely to involve bone metastasis without a specific tendency to develop visceral metastasis, implying the unique significance of bone metastasis from breast cancer . More than 70% of breast cancer deaths can be attributed to bone metastasis from breast cancer, which is 60% greater than the next common metastasis pattern, validating the significance and urgency of our research on bone metastasis from breast cancer. …”
Section: Introductionmentioning
confidence: 99%